2023
DOI: 10.1186/s12957-022-02884-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum procalcitonin improves diagnosis of infectious complications after CRS/HIPEC

Abstract: Background Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) improve the survival of selected patients with peritoneal metastasis. A major cause of treatment-related morbidity after CRS/HIPEC is infection and sepsis. HIPEC alters the diagnostic sensitivity and specificity of blood and serum markers and therefore has an impact on early diagnosis of postoperative complications. This study aimed to assess the sensitivity and specificity of blood and serum markers af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Recently, numerous studies have shown that white blood cell (WBC) count, C-reactive protein (CRP), and procalcitonin (PCT) are used to predict postoperative infectious complications [ 6 – 8 ]. However, the value of PCT and CRP levels in predicting infectious complications remains controversial [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies have shown that white blood cell (WBC) count, C-reactive protein (CRP), and procalcitonin (PCT) are used to predict postoperative infectious complications [ 6 – 8 ]. However, the value of PCT and CRP levels in predicting infectious complications remains controversial [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%